Postur Kerja Duduk, Gerakan Berulang, Dan Keluhan Ekstremitas Atas Pada Pekerja Bagian Pelintingan Rokok Cv.Suud Bondowoso - Restya Arni Priyanto; Isa Ma’rufi; Ragil Ismi Hartanti (Pascasarjana Universitas Jember, 2020)
The process of rolling cigarettes in CV. SUUD Bondowoso performed by workers by sitting down in varying manners according to the posture of the worker. Work desks, work chairs, and manual cigarettes rolling equipment are provided by the factory in uniform. Although even though they are similar in size, differences in posture can cause workers' seating positions to vary. The process of rolling cigarettes in CV. SUUD Bondowoso uses repetitive processes to meet the factory’s targets. The type of research used in this study is descriptive research. The respondents in the study were 21 workers in the manual cigarettes rolling division of CV. SUUD Bondowoso. The variables examined in this study were age, working period, sitting position, repetitive movements, and upper extremity symptoms for workers workers at manual cigarettes rolling division in CV. SUUD Bondowoso. The results showed that most respondents had posture at level 2. Eight respondents performed repetitive movements at work that fall into the high frequency category on the upper arm, elbow, arm, and wrist. Respondents with low-risk upper extremity symptoms as many as 14 people and respondents with moderate-risk upper extremity symptoms were 7 people. All respondents experienced complaints on the lower neck and right upper arm. Keywords: sitting work posture, repetitive motions, upper extremity symptoms, cigarettes rolling